KAWRUH PAMOMONG: CHILDREN EDUCATION BASED ON LOCAL WISDOM IN YOGYAKARTA - Dhiniaty Gularso; Sugito Sugito; Zamroni Zamroni (LPMPP Universitas Negeri Yogyakarta, 2019)
Character education is the fundamental thing for one’s future. In Indonesia, especially in Yogyakarta, the education of local wisdom based is Kawruh Pamomong. It is to educate children based on the truthfulness, love/passion and beautifulness or gracefulness. This research aims at studying and mapping the family education based on local wisdom Kawruh Pamomong Ki Ageng Suryomentaram in the sub-village of Balong of Timbulharjo Village in the sub-district of Sewon, Bantul Regency of Yogyakarta. Balong is a sub-district in the Southern of Yogyakarta, well-known for its KawruhJiwa in Yogyakarta. This research is conducted to gain information about how parents teach the children to think and act properly, passionate and nice. Survey method was employed in this research. The data were gained from 30 children and adolescences, in form of questionnaire, the citizens of Balong sub-district. The result of the research indicates that father and mother share the common competence in teaching and applying the Kawruh Pamomong of truthfulness and “sih”, in Kawruh Pamomong of truthfulness, father has the higher competence than mother.